Mechanical and dimensional properties of bamboo (Gigantochloa Scortechinii) fiber - thermoplastic composite / Jamaludin Kasim, Veronica Sintan and Abd. Latif Mohmod - Kasim, Jamaludin; Sintan, Veronica; Mohmod, Abd. Latif (Universiti Teknologi MARA Cawangan Pahang, 2005)
Bamboo fibres, retained at the screen size of 1.0 mm were used in the production of bamboo plastic composites at three different plastic: bamboo ratio (30:70, 50:50 & 70:30 w/w). Two plastic material namely high density polypropylene (HDPP) and low density polyethylene (LDPE) and a 3% maleated anhydride polypropylene (MAPP) on the total weight were used as the compatibilizer. Both plastic material and plastic: bamboo ratio had significant effect on all the board properties (except for plastic: bamboo ratio on MOR). Higher fibre content increases the board stiffness but with acceptable modulus of rupture (MOR) and tensile (TEN) strength values. However, higher fibre content decreased the WA and TS properties. Thermoplastic boards with polypropylene as the matrix shows better strength but lower dimensional properties compared with boards blended with polyethylene